Enhancing diagnosis and treatment of superior cluneal nerve entrapment: cadaveric, clinical, and ultrasonographic insights - Wu, Wei-Ting; Mezian, Kamal; Naňka, Ondřej; Chen, Lan-Rong; Ricci, Vincenzo; Lin, Chih-Peng; Chang, Ke-Vin; Özçakar, Levent (Insights into imaging, 2023)
OBJECTIVES: Low back pain is a prevalent public health issue caused by superior cluneal nerve (SCN) entrapment. This study aimed to explore the course of SCN branches, cross-sectional area (CSA) of the nerves, and effects of ultrasound-guided SCN hydrodissection. METHODS: SCN distance relative to the posterior superior iliac spines was measured and compared with ultrasound findings in asymptomatic volunteers. The CSA of the SCN, pressure-pain threshold, and pain measurements were obtained from asymptomatic controls and patients with SCN entrapment at various time points after hydrodissection (with 1 mL of 50% dextrose, 4 mL of 1% lidocaine, and 5 mL of 1% normal saline) in the short-axis view. RESULTS: Twenty sides of 10 formalin-fixed cadavers were dissected. The SCN locations on the iliac crest did not differ from the ultrasound findings in 30 asymptomatic volunteers. The average CSA of the SCN across different branches and sites ranged between 4.69-5.67 mm2 and did not vary across different segments/branches or pain statuses. Initial treatment success was observed in 77.7% (n = 28) of 36 patients receiving hydrodissection due to SCN entrapment. A group with initial treatment success experienced symptom recurrence in 25% (n = 7) of cases, and those with recurrent pain had a higher prevalence of scoliosis than those without symptom recurrence. CONCLUSIONS: Ultrasonography effectively localizes SCN branches on the iliac crest, whereby increased nerve CSA is not useful for diagnosis. Most patients benefit from ultrasound-guided dextrose hydrodissection; however, those with scoliosis may experience symptom recurrence and whether structured rehabilitation can reduce recurrence post-injection should be considered as one perspective in future research. Trial registration ClinicalTrials.gov (NCT04478344). Registered on 20 July 2020, https://clinicaltrials.gov/ct2/show/NCT04478344?cond=Superior+Cluneal+Nerve&cntry=TW&draw=2&rank=1 . Critical relevance statement Ultrasound imaging accurately locates SCN branches on the iliac crest, while enlargement of the CSA is not useful in diagnosing SCN entrapment; however, approximately 80% of SCN entrapment cases respond positively to ultrasound-guided dextrose hydrodissection.
Keywords: Low back pain; Hydro-dissection; Neuropathy; Dextrose; Sonography